Developing an Ideal Change Management Framework for Enhancing Service Delivery in Government Parastatals: A Case Study of Kampala Capital City Authority in Uganda. - Odeke, Paul; Okech, Benson (Journal of Business and Strategic Management, 2024)
Purpose: This study aims to develop an ideal change management framework specifically tailored to government parastatals in Uganda, focusing on the Kampala Capital City Authority (KCCA), to enhance service delivery. Methodology: The research adopted a cross-sectional and exploratory approach, utilizing both quantitative and qualitative methods. The study population comprised 298 participants from various departments within KCCA. Data collection involved self-administered questionnaires, interviews with key informants, and documentary review. Validation of study instruments was conducted using the Content Validity Index, and reliability was assessed through Cronbach’s Alpha coefficient. Quantitative data were analyzed using descriptive statistics, correlation analysis, and bivariate regression, while qualitative data underwent content analysis. Findings: The study concluded that the change management process for service delivery in government parastatals in Uganda is well-defined. However, the ideal change management framework necessary for improving service delivery among these parastatals remains unidentified. Recommendations: Based on the findings, it is recommended that KCCA administrators adopt a more holistic approach to change management, addressing various enabling factors and components necessary to enhance service delivery effectively.